GABA and Glx levels in cortico-subcortical networks predict catecholaminergic effects on response inhibition - Koyun, Anna Helin; Werner, Annett; Kuntke, Paul; Roessner, Veit; Beste, Christian; Stock, Ann-Kathrin (Journal of psychopharmacology (Oxford), 2025)
Background: Cortico-subcortical networks play a fundamental role in cognitive control. Within these circuits, neurotransmitters such as gamma-aminobutyric acid (GABA), glutamate, and catecholamines crucially modulate response control and (motor) response inhibition. Despite the evident interrelation between these transmitter systems, the role of baseline GABA and glutamate-glutamine (Glx) levels in predicting/influencing catecholaminergic effects has remained rather unclear. Aims: Addressing this knowledge gap, we investigated the question how much (and which facets) of behavioral effects attributed to catecholamines are due to GABAergic and glutamatergic levels in control-relevant cortical networks. Methods: Using proton-magnetic resonance spectroscopy, we assessed baseline GABA+ and Glx levels within the striatum, the anterior cingulate cortex, and the (pre-)supplementary motor cortex ((pre-)SMA), and their predictive value for catecholaminergic modulation of response selection and inhibition performance. For this purpose, we administered low and high doses of methylphenidate (MPH) to healthy adults and examined whether baseline GABA+ and Glx were associated with dose-dependent MPH effects on response control. Results/Outcomes: For the first time in a sample of healthy adults, we demonstrate that GABA+/Glx levels in cognitive control-relevant cortical areas are indicative of the magnitude of MPH-induced effects on response inhibition. Specifically, striatal GABA+/Glx levels predicted better response inhibition performance under the administration of low MPH doses. In contrast, (pre-)SMA GABA+/Glx levels were associated with high MPH dose-induced impairments of response inhibition performance. Conclusion/Interpretation: The predictive relevance of GABA+/Glx levels for MPH dose-dependent effects on cognitive control processes provides valuable insights into the neural mechanisms underlying the previously reported heterogeneous MPH effects.